ICAM-1 Participates in the Entry of West Nile Virus into the Central Nervous System - Dai, Jianfeng (American Society for Microbiology (ASM), 2008)
Determining how West Nile virus crosses the blood-brain barrier is critical to understanding the pathogenesis of encephalitis. Here, we show that ICAM-1(−/−) mice are more resistant than control animals to lethal West Nile encephalitis. ICAM-1(−/−) mice have a lower viral load, reduced leukocyte infiltration, and diminished neuronal damage in the brain compared to control animals. This is associated with decreased blood-brain barrier leakage after viral infection. These data suggest that ICAM-1 plays an important role in West Nile virus neuroinvasion and that targeting ICAM-1 signaling may help control viral encephalitis.